Evaluation of Dentinal Thickness and Remaining Dentine Volume around Root Canals Using Cone-Beam Computed Tomography Scanning - Svetlana Razumova; Anzhela Brago; Haydar Barakat; Dimitriy Serebrov; Zoya Guryeva; Gleb S. Parshin; Vasiliy I. Troitskiy (MDPI AG, 2023)
Background: The remaining dentinal thickness is a significant factor to deal with when planning post-endodontic treatment. Aim: To assess the changes in the root canal dentinal thickness of intact and endodontically treated teeth using CBCT scans in the coronal, middle, and apical third of the root canal. Material and methods: Three hundred CBCT scans for three age groups were analyzed to study the dentinal thickness pre- and post-endodontic treatment. The dentinal thickness (DT) was measured along the buccal, mesial, distal, and lingual/palatal walls from the inner surface of the root canal to the outer surface in mm. Statistical analysis was set at 0.05. Results: The results of this study showed that the buccal, palatal, distal, and mesial dentinal thickness in intact and endodontically treated teeth is different. The differences were statistically significant when comparing the parameters of "healthy" and "treated" teeth (p < 0.05). There were no statistically significant differences in indicators associated with age (p > 0.05). In the coronal third of the root canal, the least amount of dentin tissue lost was 4.2% for mandibular canines. Conclusions: The dentinal thickness in the coronal and middle third of the root decreases significantly more than the apical third. The most loss of dentine volume was among molar teeth, and the remaining dentinal thickness was less than 1 mm, which would increase the risk of complication while preparing the canal for a post.